Pendaftaran Prosedur Sertifikasi Halal MUI Bagi UMKM Dimsum NN - Rinjani, Diliya Mariam; Hamidah, Syifa Fauziah; Hambali, M. Shany (Jurnal Pengabdian Tri Bhakti, 2023)
Every year food trends emerge, both food trends originating from Indonesia and food trends originating from abroad, one of which is dimsum. The public's interest in Dimsum culinary originating from China is great, but because it comes from a country where the majority of the people are non-Muslims, the halalness of this type of Dimsum culinary is often questioned. The purpose of this PKM activity is to help these MSMEs with registration for MUI halal certificates, and then assist digital marketing through online market places and social media. The method used in this service activity is direct observation to the location, conducting counseling/education, training, demonstrations and mentoring to partners, then helping to register the NIB and then helping to register the halal certification. As a result, MSME partners can understand the importance of halal certificates for the products they sell to increase consumer confidence.